2007
DOI: 10.1093/annonc/mdl408
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal toxicity and osteonecrosis of the jaws in patients receiving zoledronic acid for bone metastasis

Abstract: ZA showed to be safe with a low rate of reversible renal toxicity. Patients receiving BP should be monitored carefully for renal toxicity and ONJ, especially those with exposure to BP beyond 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Multiplicity and longer duration (>2 years) increase the risk. 93 The median time to occurrence is 4.7–5.4 months. 94 95 The risk for acute renal failure increases in low creatinine clearance rates (CCR, <60 mL/min).…”
Section: Treatmentsmentioning
confidence: 99%
“…Multiplicity and longer duration (>2 years) increase the risk. 93 The median time to occurrence is 4.7–5.4 months. 94 95 The risk for acute renal failure increases in low creatinine clearance rates (CCR, <60 mL/min).…”
Section: Treatmentsmentioning
confidence: 99%
“…Ali et al [23] found BP safe and well tolerated in 22 patients treated for a median of 3.6 years. In an other study, 57 patients were treated for a median of 34 months: grade 1 nephrotoxicity was reported in 12.2% of them [22] Bujanda et al [24] found an overall 9% incidence of nephrotoxicity in 67 patients analysed (18% in the group treated for [2 years).…”
Section: Discussionmentioning
confidence: 94%
“…The American Society of Clinical Oncology guidelines for BP in BC suggests treating patients for as long their performance status does not deteriorate [21], but there are still few data concerning their safety and efficacy in patients treated for more than 2 years [22][23][24]. Ali et al [23] found BP safe and well tolerated in 22 patients treated for a median of 3.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dog received 4 mg of zoledronic acid diluted in 100 ml of saline solution every 28 days in a slow intravenous infusion over 30 minutes. The dog had a complete blood cell count and a biochemical profile checked before each zoledronate infusion and a thorough oral examination and jaw radiographs every six months to rule out bisphosphonate‐induced bone necroses (Aguiar Bujanda and others 2007, Wilkinson and others 2007).…”
Section: Case Reportmentioning
confidence: 99%